(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The article discusses the concept of pragmatics in the study of linguodidactics with particular focus on the principles and methods of the development of pragmatic competence in foreign language, especially English language education in university-level learning context. In addition, the paper reflects the most significant tools and techniques to explore the assessment of linguistic and communicative knowledge encountered in academic English reading assessment tasks which also integrate the testing of pragmatic ability of students and test-takers in learning and testing situations.